The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1074/jbc.m115.708065
|View full text |Cite
|
Sign up to set email alerts
|

Energetic Mechanism of Cytochrome c-Cytochrome c Oxidase Electron Transfer Complex Formation under Turnover Conditions Revealed by Mutational Effects and Docking Simulation

Abstract: Based on the mutational effects on the steady-state kinetics of the electron transfer reaction and our NMR analysis of the interaction site (Sakamoto, K., Kamiya, M., Imai, M., Shinzawa-Itoh, K., Uchida, T., Kawano, K., Yoshikawa, S., and Ishimori, K. (2011) Proc. Natl. Acad. Sci. U.S.A. 108, 12271-12276), we determined the structure of the electron transfer complex between cytochrome c (Cyt c) and cytochrome c oxidase (CcO) under turnover conditions and energetically characterized the interactions essential f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 60 publications
7
29
0
Order By: Relevance
“…Amino-acid residues included in the catalytic binding were assigned based on the Cyt.c-CcO complex structure equilibrated in a solution in which the enzyme exerts its normal catalytic activity (Yonetani & Ray, 1965). The interactions between Cyt.c and CcO elucidated by this crystallographic study are consistent with those revealed for the enzyme-substrate complex under turnover conditions by previous experimental studies involving chemical modifications and kinetics (Ferguson-Miller et al, 1978) or solution NMR and kinetics for complexes containing wild-type and mutant Cyt.c proteins (Sakamoto et al, 2011;Sato et al, 2016).…”
Section: Catalytic Binding Sitessupporting
confidence: 89%
See 2 more Smart Citations
“…Amino-acid residues included in the catalytic binding were assigned based on the Cyt.c-CcO complex structure equilibrated in a solution in which the enzyme exerts its normal catalytic activity (Yonetani & Ray, 1965). The interactions between Cyt.c and CcO elucidated by this crystallographic study are consistent with those revealed for the enzyme-substrate complex under turnover conditions by previous experimental studies involving chemical modifications and kinetics (Ferguson-Miller et al, 1978) or solution NMR and kinetics for complexes containing wild-type and mutant Cyt.c proteins (Sakamoto et al, 2011;Sato et al, 2016).…”
Section: Catalytic Binding Sitessupporting
confidence: 89%
“…Recent site‐directed mutagenesis and kinetics studies of Cyt. c indicated that the ET activities of K13L, K86L/K87L, and K7L/K8L mutants are significantly lower than that of the wild‐type protein (Sato et al , ). The side chains of Lys 8 , Gln 12 , Lys 13 , and Lys 87 of Cyt.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Native and 15 N-labeled human Cyt c were expressed in Escherichia coli and purified as previously described [11,12]. Briefly, Rosetta2(DE3)pLysS (Novagen, Madison, WI) cells transformed with the plasmids containing human Cyt c [25] DNA were inoculated in 5 mL 2xYT medium and grown overnight.…”
Section: Protein Expression and Purificationmentioning
confidence: 99%
“…To oxidize the residual ferrous form, horse heart Cyt c (Merck Millipore, Darmstadt, Germany) was treated with potassium ferricyanide (Wako Pure Chemical Industries Ltd.) and was purified on an Amicon ultrafiltration using 5-kDa cutoff membranes to remove excess oxidants. The expression vector for the Cyt c mutant containing Gln at the His26 position was constructed as per Sato, W. et al [28]. The protein was dissolved in 50 mM Tris-HCl buffer (pH 7.5) at various activities of urea (molecular biology grade from Kanto Chemical Co., Inc., Tokyo, Japan) or GdnHCl (biochemistry grade from Kanto Chemical Co.) before the experiments.…”
Section: Determination Of Volume Changes In Protein Unfoldingmentioning
confidence: 99%